Dynamic of container with fluid - Wang, Zhiwen. (2009)
Container/tank has been used widely in industries for transport of fluid as well as storage of water. Damage to storage tank due to seismic activity and construction of oil tanks have sparked off an interest in scholars and researchers to look into the static and dynamic analysis of a tank containing fluid. However, most of the studies are on cylindrical tanks, with studies on rectangular tanks far and few.